2000
DOI: 10.1046/j.1469-8137.2000.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

A thermal time basis for comparing the germination requirements of some British herbaceous plants

Abstract: The effect of temperature on germination rate was assessed for seeds of 31 wild plant species and four cultivated species growing in the UK. The temperature at which seed first germinated ranged from 2mC (Brassica rapa) to 11mC (several species). As the temperature progressively increased, the percentage of seed that germinated rapidly increased to near 100%, whereas the duration for germination progressively decreased up to the thermal optimum. Above the thermal optimum, the duration for germination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 20 publications
(36 reference statements)
6
64
2
Order By: Relevance
“…Among the 27 species in this study, the differences in base temperature were not significant between annuals and perennials, but the differences in thermal time constant were significant between annuals and perennials (16.0 °C·d and 26.2 °C·d, respectively; p < 0.01). This result was consistent with previous research [17], which indicated that germination responses to temperature was related to plant life cycle. Compared to tropical and subtropical legumes [18], the temperate grassland species in our study had lower base temperature and thermal time constants.…”
Section: Comparison Of Model Parameters Between C3 and C4 Speciessupporting
confidence: 94%
See 1 more Smart Citation
“…Among the 27 species in this study, the differences in base temperature were not significant between annuals and perennials, but the differences in thermal time constant were significant between annuals and perennials (16.0 °C·d and 26.2 °C·d, respectively; p < 0.01). This result was consistent with previous research [17], which indicated that germination responses to temperature was related to plant life cycle. Compared to tropical and subtropical legumes [18], the temperate grassland species in our study had lower base temperature and thermal time constants.…”
Section: Comparison Of Model Parameters Between C3 and C4 Speciessupporting
confidence: 94%
“…However, most studies use the thermal time model to investigate intraspecific variation of germination or differences between several species [3,[14][15][16]. However, comparison of thermal time model parameters between large numbers of species and between different functional groups is lacking [17,18]. Knowing and comparing the base temperature and thermal time constant at the species level can increase our ability to predict species distribution shift under climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, T opt is defined as the temperature at which germination is most rapid and it was reported that FGP correlates linearly with GR 50% at temperatures lower than T opt , whereas the both measures are usually decoupled at higher temperatures (Trudgill et al 2000). Thus, these two measures of germination may have different ecological relevance, but the underlying relations are not yet examined adequately.…”
Section: Germination Responses To Temperaturementioning
confidence: 99%
“…Olff et al (1994) illustrated that germination characteristics can be used to explain species occurrence in a lowland secondary succession. The optimum temperature of germination (T opt ) is commonly speciesspecific (Trudgill et al 2000) and affects the regeneration in terms of emergence timing and abundance of seedlings (Probert 2000). Although the germination responses of various alpine species have been widely investigated with respect to temperature (Billings and Mooney 1968;Cavieres and Arroyo 2000;Giménez-Benavides et al 2005;Shimono and Kudo 2005;Wagner and Simons 2009), knowledge on temperature ranges and T opt of alpine species is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This is now frequently used to integrate more complex biological processes inpoikilothermic species, supporting some practical and ecological implications (Trudgill et al 2005). Thermal time has been used to analyse the effect of temperature on germination or both germination and emergence in non-limiting moisture conditions of several commercial herbaceous species (Moot et al 2000;Trudgill et al 2000;Larsen & Bibby 2005;Black et al 2006). A mathematical model to describe germination percentage dependency on time and temperature in Amaranthus patulus under sub-optimal temperature conditions has also been developed (Washitani & Takenaka 1984).…”
Section: Introductionmentioning
confidence: 99%